1972
DOI: 10.1128/am.24.1.91-95.1972
|View full text |Cite
|
Sign up to set email alerts
|

Chromatography of Venezuelan Equine Encephalomyelitis Virus Strains on Calcium Phosphate

Abstract: Column chromatography of selected Venezuelan equine encephalomyelitis (VEE) viruses on calcium phosphate gel offered a simple and reproducible method for examination of biochemical characteristics and relatedness of strains within the VEE complex. Members of antigenic subgroup I demonstrated a series of elution profiles within a narrow range of 0.22 to 0.25 M phosphate buffer. Members of antigenic subgroups II, III, and IV differed substantially among themselves and viruses of antigenic subgroup I. These diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1973
1973
1977
1977

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Since elution profiles are strongly influenced by changes in pH or gradient dimensions, it is difficult to compare our results with those reported by other investigators who have used similar, but not identical, techniques for alphaviruses. Pedersen et al (12) reported that the elution peaks for VEE strains eluted from calcium phosphate columns at pH 7.4 ranged from 0.25 to 0.32 M phosphate. Fleming (7) reported that SF virus strains were eluted from hydroxylapatite columns by 0.6 to 0.7 M phosphate at pH 8.0 to 8.2, similar to our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since elution profiles are strongly influenced by changes in pH or gradient dimensions, it is difficult to compare our results with those reported by other investigators who have used similar, but not identical, techniques for alphaviruses. Pedersen et al (12) reported that the elution peaks for VEE strains eluted from calcium phosphate columns at pH 7.4 ranged from 0.25 to 0.32 M phosphate. Fleming (7) reported that SF virus strains were eluted from hydroxylapatite columns by 0.6 to 0.7 M phosphate at pH 8.0 to 8.2, similar to our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The applications of column chromatography methods, using calcium phosphate or its derivatives, to the purification and characterization of numerous viruses have been reported (4,5,7,(11)(12)(13). This paper describes procedures using the hydroxylapatite form of calcium phosphate to effect satisfactory separations of selected alphavirus strains including Western equine encephalomyelitis virus (WEE), Eastern equine encephalomyelitis virus (EEE), and Semliki Forest virus (SF) strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation